Distal Vagina Smooth Muscle Contractility Mechanisms: Effects of in Vivo Sex Steroids Treatment in an Animal Experimental Model of Ovariectomy. (1st August 2022) - Cipriani, S; Cellai, I; Comeglio, P; Filippi, S; Martinelli, S; Amore, F; Rapizzi, E; Maseroli, E; Raddi, C; Guarnieri, G; Sarchielli, E; Morelli, A; et al.
ABSTRACT: Introduction: Female sexual response is a complex phenomenon that involves multiple psychophysiological factors. Sex steroids play a fundamental role in the mechanisms of regulation of sexual arousal, modulating the sexual response and preserving the integrity and functionality of the vaginal tissue. For this reason, imbalances in the sexual environment of steroids in women favor the onset of important pathophysiological conditions such as hypoactive sexual desire disorder (HSDD) and genitourinary syndrome of menopause (GSM). Previous research has focused primarily on the effects of estrogen supplementation on vaginal physiology, but only few studies evaluated the effects of androgen administration, particularly on the vaginal smooth muscle compartment. The calcium sensitizing pathway of RhoA/ROCK may play a role in regulating vaginal contractility but, at present, the regulatory mechanisms of RhoA/ROCK signaling in the female genitourinary tract have yet to be fully elucidated. In particular, no specific research has been conducted on the effects of testosterone (T) on the contractility mechanism of smooth muscle in the vagina. Objective: The aim of this study was to evaluate the sex steroid regulation on the distal vagina contractility mechanism, mediated by the RhoA/ROCK pathway, using a validated animal model of female ovariectomized rats. Methods: Ovariectomized Sprague-Dawley rats (OVX) were treated with 17β-estradiol (OVX+E), testosterone (OVX+T), or testosterone and letrozole (OVX+T+L) and compared with an intact animals' group (CTRL). In vitro contractility studies were performed on noradrenaline (NA) pre-contracted vaginal strips to investigate the effect of OVX and in vivo treatments on vaginal smooth muscle activity. The mRNA from vagina tissues isolated from each experimental group was analyzed by semi-quantitative RT-PCR, and membrane translocation of RhoA was evaluated by Western blot analysis. Results: Y-27632 induced a dose-dependent relaxation on NA pre-contracted vaginal strips that was significantly decreased by OVX; T, with or without L, further decreased OVX-induced hyporesponsiveness to Y-27632, whilst it was fully restored up to control level by 17β-estradiol (E) supplementation. Accordingly, gene expression analysis indicated that OVX decreased the expression of RhoA/ROCK pathway markers, which was normalized by E. However, at variance with contractility results, androgen receptor (AR) activation upregulated, rather than downregulating, RhoA/ROCK expression. In Western blot analysis, OVX induced activation and membrane translocation of the active form of RhoA as compared to controls. Interestingly, T reverted this effect by reducing RhoA translocation to membrane to a level even significantly below the control one. This effect was not exerted by E administration. Considering that AR activation increases NO signaling (as measured by Prkg1 mRNA expression), we tested the effect of abolishing NO formation through the NO synthase inhibitor L-NAME. Pre-incubation with L-NAME substantially increased Y-27632 responsiveness in the OVX +T group and partially in the CTRL one and, but not in the OVX group. Conclusions: This study confirms that in vagina estrogens increase the expression of the calcium-sensitizing pathway RhoA/ROCK, while androgen administration functionally decreases RhoA/ROCK activity, by hampering RhoA translocation to the membrane, a mechanism which is most probably driven by NO. Disclosure: No